The Role of Oxidative Stress and Hypoxia in Pancreatic Beta-Cell Dysfunction in Diabetes Mellitus - Gerber, Philipp A; Rutter, Guy A (Antioxidants & redox signaling, 2017)
Metabolic syndrome is a frequent precursor of type 2 diabetes mellitus (T2D), a disease that currently affects ∼8% of the adult population worldwide. Pancreatic beta-cell dysfunction and loss are central to the disease process, although understanding of the underlying molecular mechanisms is still fragmentary. Recent Advances: Oversupply of nutrients, including glucose and fatty acids, and the subsequent overstimulation of beta cells, are believed to be an important contributor to insulin secretory failure in T2D. Hypoxia has also recently been implicated in beta-cell damage. Accumulating evidence points to a role for oxidative stress in both processes. Although the production of reactive oxygen species (ROS) results from enhanced mitochondrial respiration during stimulation with glucose and other fuels, the expression of antioxidant defense genes is unusually low (or disallowed) in beta cells. Not all subjects with metabolic syndrome and hyperglycemia go on to develop full-blown diabetes, implying an important role in disease risk for gene-environment interactions. Possession of common risk alleles at the SLC30A8 locus, encoding the beta-cell granule zinc transporter ZnT8, may affect cytosolic Zn concentrations and thus susceptibility to hypoxia and oxidative stress. Loss of normal beta-cell function, rather than total mass, is increasingly considered to be the major driver for impaired insulin secretion in diabetes. Better understanding of the role of oxidative changes, its modulation by genes involved in disease risk, and effects on beta-cell identity may facilitate the development of new therapeutic strategies to this disease. Antioxid. Redox Signal. 26, 501-518.